Biomechanical Comparison of a 3-Loop Pulley and a 4-Loop Pulley Suture for Tenorrhaphy in the Canine Gastrocnemius Tendon - O'Byrne, Kadie L.; Sugiyama, Takanori; Robinson, Dale; Woodward, Andrew P.; Ryan, Stewart D. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to compare a 3-loop pulley (3LP) suture pattern with a 4-loop pulley (4LP) suture pattern for the tenorrhaphy of the canine gastrocnemius tendonStudy Design Randomized, cadaveric, biomechanical study of 30 canine gastrocnemius tendons. Tendons were transected and repaired with either 3LP or 4LP suture pattern with 2–0 polypropylene. A tensile load was applied at 25 mm/min until construct failure. The load required to form a 1 mm gap, 3 mm gap and maximum load at failure was recorded and compared between groups.Results The estimated mean load to form a 1 mm gap for the 3LP and 4LP was 28.4 N (95% confidence interval [CI]: 24.0–32.6N) and 45.5 N (95% CI: 40.7–50.1N) respectively. The 4LP mean load to form a 1 mm gap was 17.1 N (95% CI: 11.7–22.5N) greater than the 3LP. The estimated mean load to form a 3mm gap for the 3LP and 4LP was 39.7 N (95% CI: 34.1–45.4N) and 55.0 N (95% CI: 49.3–60.9N) respectively. The mean load to form a 3mm gap was 15.3 N (95% CI: 8.5–21.9N) greater in the 4LP than the 3LP. The estimated mean load for failure in the 3LP and 4LP was 41.2 N (95% CI: 35.6–46.9 N) and 54.3 N (95% CI: 48.7–60.3 N) respectively.Conclusion A 4LP pattern was biomechanically superior to a 3LP pattern, as demonstrated by a greater load required to form both a 1 and 3 mm gap and a greater load for failureClinical Significance A 4LP suture pattern better resists gap formation and requires greater load prior to construct failure compared with a 3LP, in this canine gastrocnemius model
Keywords: biomechanical; tendon repair; mechanical testing; tendon healing; tendon injuries